The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/ccm.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

International Study on Microcirculatory Shock Occurrence in Acutely Ill Patients*

Abstract: In a heterogeneous ICU population, an abnormal microvascular flow index was present in 17% of patients. This was not associated with mortality. However, in patients with tachycardia, an abnormal microvascular flow index was independently associated with an increased risk of hospital death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 60 publications
6
95
0
1
Order By: Relevance
“…Thus, oral microcirculation is not an indicator of gastrointestinal microcirculation and organ function per se, especially if flow only is analyzed, without an assessment of oxygenation. This might explain the results of the recently published international study on microcirculatory shock occurrence in acutely ill patients (microSOAP) [32]. The study found a 17% prevalence of abnormal capillary microvascular flow index among 501 patients.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, oral microcirculation is not an indicator of gastrointestinal microcirculation and organ function per se, especially if flow only is analyzed, without an assessment of oxygenation. This might explain the results of the recently published international study on microcirculatory shock occurrence in acutely ill patients (microSOAP) [32]. The study found a 17% prevalence of abnormal capillary microvascular flow index among 501 patients.…”
Section: Discussionsupporting
confidence: 71%
“…Since the landmark paper by De Backer et al [1], numerous studies have addressed microcirculatory dysfunction in septic shock, established its pathophysiological relevance, and demonstrated the prognostic impact of persistent abnormalities [2][3][4][5]. Sublingual microcirculation, which is easy to access with video-microscopic techniques, is the most frequently explored territory in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several direct microcirculation monitoring techniques have also been devised [57]. Although initial studies have shown some correlation between mortality and the direct microcirculation measurement in early ICU admissions (≤48 h) [58,59,60], the results have not been consistent, especially in heterogeneous ICU patients [61]. Moreover, in their current state, the methods require cumbersome offline data analysis, not yet feasible for routine bedside use.…”
Section: Fluid Requirement In Healthy and In Hospitalized Patientsmentioning
confidence: 99%